Identifying Cohorts Using Isotope Mass Spectrometry: The Potential of Temporal Resolution and Dietary Profiles. (27th February 2021) - Beaumont, Julia; Bekvalac, Jelena; Harris, Samuel; Batt, Catherine M.
Abstract : Archaeological skeletal material from most sites represents a cross‐sectional, opportunistic sample of the burials. These are influenced by the proportion and area of the site that is excavated, the taphonomic conditions, and survival of tissues. This may not be representative of the population, and in an attritional cemetery may represent a long period of use, during which humans will have differing life courses. Here we describe a commingled skeletal assemblage, the only human remains recovered from the historically significant medieval site of St Stephen's Chapel, Palace of Westminster, London. Using carbon (δ 13 C) and nitrogen (δ 15 N) stable isotope ratios of bulk bone collagen and incremental dentine to investigate dietary life histories from five individuals, we combine the evidence with radiocarbon dating to assign them to two different temporal cohorts.